Building an Analytical Method to Study Cantilever Beam Dynamic Response - M.Sarhan, Samaher (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Cantilever beams are used in many crucial applications in machinery and construction. For example, the airplane wing, the microscopic probe for atomic force measurement, the tower crane overhang and twin overhang folding bridge are typical examples of cantilever beams. The current research aims to develop an analytical solution for the free vibration problem of cantilever beams. The dynamic response of AISI 304 beam represented by the natural frequencies was determined under different working surrounding temperatures ((-100 ℃ to 400 ℃)). A Matlab code was developed to achieve the analytical solution results, considering the effect of some beam geometrical dimensions. The developed analytical solution has been verified successfully with real experimental data and the error was not exceeded 1%.Keywords: analytical solution, cantilever beam, free vibration, mathematical modeling.